Expert and fuzzy systems application for information security risks assessment of information and telecommunication systems (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2012)
The risks assessment is one of the main stages during the development and maintenance processes of the secure information and telecommunication systems (ITS). The expert and fuzzy systems application for information security risks assessment of information-telecommunication systems is considered in this paper. The risks assessment is held for the sample ITS using CRAMM and MSAT expert systems and fuzzy expert system. The results are compared. Recommendations are given for expert and fuzzy systems application during information security risks assessment.